2010
DOI: 10.1155/2010/254159
|View full text |Cite
|
Sign up to set email alerts
|

EnteroaggregativeEscherichia coli: An Emerging Enteric Food Borne Pathogen

Abstract: Enteroaggregative Escherichia coli (EAEC) are quite heterogeneous category of an emerging enteric pathogen associated with cases of acute or persistent diarrhea worldwide in children and adults, and over the past decade has received increasing attention as a cause of watery diarrhea, which is often persistent. EAEC infection is an important cause of diarrhea in outbreak and non-outbreak settings in developing and developed countries. Recently, EAEC has been implicated in the development of irritable bowel synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 101 publications
(110 reference statements)
6
73
0
1
Order By: Relevance
“…Studies have shown a wide selection of EAEC serotypes and many are untypeable [30][31][32]; therefore, serotyping is not a useful tool in distinguishing this problematic group.…”
Section: Enteroaggregative E Coli (Eaec)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown a wide selection of EAEC serotypes and many are untypeable [30][31][32]; therefore, serotyping is not a useful tool in distinguishing this problematic group.…”
Section: Enteroaggregative E Coli (Eaec)mentioning
confidence: 99%
“…Thank you to the authors of published MLST data [18,24,32] which was used for the analysis in this paper.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…[6][7][8] Also, EAEC has been identified as a common cause of acute diarrheal illness in children and adults in inpatient and emergency units throughout the United States. 9 The alarming rise in attention to EAEC led to its inclusion on the National Institutes of Health category B list of infectious organisms of potential importance as a bioterrorism weapon in 2002. 10 In May 2011 an outbreak of E. coli O104:H4 occurred in Germany where more than 4,000 people became victims to infection and 54 of these cases resulted in death; the highest frequency of deaths ever recorded for an E. coli outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…EAEC is associated with traveler's diarrhea [4,5], endemic chronic pediatric diarrhea [6,7] and persistent diarrhea in immunocompromised patients [8,9]. EAEC is increasingly considered as an emerging enteric pathogen [10,11]. Among the diarrheagenic E. coli pathotypes, EAEC is more heterogeneous, with limited information on the roles and importance of specific virulence genes and putative gene products.…”
Section: Introductionmentioning
confidence: 99%